Regulatory framework for Islamic financial institutions: lesson learnt between Malaysia and Indonesia - Fazlurrahman Syarif (Journal of halal product and research (JPHR), 2019)
Islamic finance is a rapidly growing stream in the Halal economy. Islamic finance is a method of banking or financing activities that are based on the Sharia law and operated by sharing the risk or divide the profits of any investment as per the agreed terms. This study discusses the forms of a regulatory framework and on the organizations that are constituted for standardizing the regulations. The paper also analyses the regulatory framework for Islamic financial institutions in Malaysia and Indonesia. The type of research used is a descriptive qualitative model. We find that both countries maintain a dual system of the regulatory framework which considers the conventional and Islamic financial system. Hence, the central bank has full authority to enact required laws and policies and to regulate the Islamic financial institutions in Indonesia and Malaysia.